SENTIMENT ANALYSIS ON PERCEPTION OF TOURISM IN DKI JAKARTA PROVINCE: CASE STUDY OF OLD CITY AND KEPULAUAN SERIBU - Winata, Supriyadi Ramdan; Pangestuty, Farah Wulandari (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2021)
The purpose of this study is to determine the perceptions of tourists in two tourist destinations in DKI Jakarta which are included in the National Tourism Strategic Area (KSPN), namely Kota Tua and Kepulauan Seribu by conducting a sentiment analysis. The analysis was carried out on traveler reviews in the form of electronic word of mouth (eWOM) submitted on the tripadvisor site. The results of the study found that in general the sentiment of tourists towards these two destinations was positive, and each year there was an increasing trend. However, based on the exploration of sentiments that have negative connotations, it is known that the problems of odor, garbage and pollution are of great concern to tourists. Other aspects of concern to tourists are the need for better governance by local governments, and the need for standard facilities and services.